ANALISIS DAN PERANCANGAN MODEL FUZZY UNTUK SISTEM PAKAR PENDETEKSI TINGKAT KESUBURAN TANAH DAN JENIS TANAMAN - Amiril Mukminin; Heru Agus Santoso; Catur Supriyanto (Program Pascasarjana Magister Teknik Informatika, Universitas Dian Nuswantoro, 2017)
Tillage that is not appropriate to the characteristics of plant type can easily causethe plants to wilt and plant growth is not maximal. These factors areoften the main cause of crop failure that is not known by the farmers. Therefore, an expert system is designed to detectthe soil fertility for types of plant using the fuzzy logic, which is expected to help the farmers in choosing the right types of plant with an appropriate of certain level of soil fertility. The measurement results obtained have been appropriate with the calculations and criteria of the land that has been entered.